Pemberdayaan Ekonomi Masyarakat melalui Pemasaran Wisata Kuliner Jajanan Tradisoional di Desa Cantuk Kabupaten Banyuwangi - Aula Izatul Aini; Muhammad Imam Khaudli; Ribut Suprapto (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2018)
The abundance potential of Natural Resource (SDA) and Human Resources (HR) are still not providing a great space for the improvement of welfare for the mothers in Cantuk village, Banyuwangi. The data shown that most of housewives of Rampan Hamlet, Cantuk Village, were still many unemployed. However, on the one hand they had culinary skills in particular and traditional cuisine. Some culinary effort had been developed, one of which attempt to make banana, one of them was the banana chip business, but this effort did not last long because the product marketing was not maximized. From the background, through Participatory Action Research (PAR) approach, mentoring housewives’ community in strengthening the capacity of traditional culinary product sales through “Jajanan Bengi Tombo Kangen” Bazaar. The results of this mentoring were able to mobilize the housewives who were members on Moslem Al-Hikmah Rampan Hamlet, and various Hamlet around Cantuk Village to initiate and realize traditional food marketing regularly. Through this Bazaar, variety housewives’ traditional products such as pancake, cenil, klepon, and other traditional food could be distributed and sold so well, as to increase their family's income from selling traditional food in